2009
DOI: 10.1007/s00125-009-1499-0
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma vitamin B12 in pregnancy is associated with gestational ‘diabesity’ and later diabetes

Abstract: Aim-To test the hypothesis that low plasma vitamin B12 concentrations combined with high folate concentrations in pregnancy are associated with higher incidence of gestational diabetes (GDM) and later diabetes.Methods-Women (N=785) attending the antenatal clinics of the Holdsworth Memorial Hospital, Mysore, India had their anthropometry, insulin resistance (Homeostasis Model Assessment) and glucose tolerance assessed at 30 weeks gestation (100g Oral Glucose Tolerance Test/ OGTT; Carpenter-Coustan criteria), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
174
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 39 publications
20
174
3
2
Order By: Relevance
“…For example, it has been suggested that poor maternal vitamin B12 status during pregnancy, which is common in Indian populations, contributes to a higher risk of type 2 diabetes in the offspring. 38,39 Several studies in the United States have also demonstrated greater insulin resistance in East Asians as compared with whites for a given BMI. 25,40,41 For example, Chinese-American and Japanese-American women were more insulin resistant than white women after adjusting for waist circumference in a large cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that poor maternal vitamin B12 status during pregnancy, which is common in Indian populations, contributes to a higher risk of type 2 diabetes in the offspring. 38,39 Several studies in the United States have also demonstrated greater insulin resistance in East Asians as compared with whites for a given BMI. 25,40,41 For example, Chinese-American and Japanese-American women were more insulin resistant than white women after adjusting for waist circumference in a large cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…Trabajos recientes ilustran la transmisión intergeneracional del riesgo para enfermedades crónicas no transmisibles. Varios estudios han mostrado que madres con una talla más corta tienen un riesgo elevado para diabetes gestacional (34)(35)(36) , el que podría incrementar el riesgo de diabetes de sus futuros descendientes (37) . Dado que la talla es un elemento insensible al cambio a través de nutrición luego de la infancia y adolescencia, los migrantes podrían mantener una talla más corta que los individuos urbanos.…”
Section: Estudios Sobre Migración Rural-urbana En El Perúunclassified
“…Previous studies have suggested that a high maternal folate concentration is associated with an increased risk of insulin resistance in children and gestational diabetes mellitus (GDM) (1). In addition, animal experiments have reported that maternal high-FA supplement promotes glucose intolerance and insulin resistance in male mouse offspring fed a high-fat diet (2).…”
mentioning
confidence: 99%